Harnessing Neurogenesis and Neuroplasticity with Stem Cell Treatment for Addictive Disorders. Issue 9 (September 2019) - Tsai, Sheng-Tzung; Liew, Hock-Kean; Li, Hao-Ming; Lin, Shinn-Zong; Chen, Shin-Yuan
Drug and alcohol addiction has become an emerging public health issue and is a great burden to patients, their families, and society. It is characterized by high relapse rates and significant morbidity and mortality, and most available treatments result in only modest improvement. These findings highlight the necessity for new approaches to treat addiction. Scientific reports in the past two decades suggest that addiction involves impaired neural plasticity and decreased hippocampal neurogenesis. Stem cell therapy and its derived neurotrophic factors can potentially target the underlying pathophysiology of addiction. Stem cell applications are showing promise in several preclinical studies and may provide new and noninvasive treatment strategies. Future clinical research is warranted to investigate whether stem cell-based therapy could support the treatment of addiction.